Beef Feedlots In Southwestern Kansas: Local Change, Perceptions, And The Global Change Context - Harrington, Lisa M.B.; Lu, Max (My University, 2002)
Cattle feedlots, some of which have a capacity of tens of thousands of head, have become a major driving force in the local economy and changing landscape of southwestern Kansas. The feedlot industry also is one of the region’s most important sources of carbonequivalent greenhouse gases. Changes to the beef industry are described, and the perceptions and attitudes of feedlot operators regarding climatic change issues and industrial change are analyzed based on a 1998 survey. The results indicate that a majority of feedlot respondents believe ‘global warming’ is mostly an unproven theory, and efforts to mitigate it are unwarranted.
Keywords: Agriculture; Perceptions; Greenhouse gas emissions; Cattle